2008
DOI: 10.1016/j.agrformet.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison and sensitivity analysis of Leaf Area Index retrievals from LAI-2000, AccuPAR, and digital hemispherical photography over croplands

Abstract: Garrigues, S.; Shabanov, N. V.; Swanson, K.; Morisette, J. T.; Baret, F; and Myneni, R. B., "Intercomparison and sensitivity analysis of Leaf Area Index retrievals from LAI-2000, AccuPAR, and digital hemispherical photography over croplands" (2008 Intercomparison and sensitivity analysis of Leaf Area Index retrievals from LAI-2000, AccuPAR, and digital hemispherical photography over croplands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(103 citation statements)
references
References 42 publications
(85 reference statements)
3
90
0
2
Order By: Relevance
“…Historic field measurements [35] also published low LAI measurements demonstrating that the relative standard deviation of LAI field measurements in the SEVI area can be up to 60%. This is confirmed by [74], who showed large discrepancies between different ground-based LAI measurements for heterogeneous and short crop canopies due to the substantial differences in the spatial sampling of transmittance (up to RMSE of 0.16). For shrub and grass land, at least the same error for the LAI measurements is expected, as well as for remote sensing-derived LAI products.…”
Section: Resultssupporting
confidence: 66%
“…Historic field measurements [35] also published low LAI measurements demonstrating that the relative standard deviation of LAI field measurements in the SEVI area can be up to 60%. This is confirmed by [74], who showed large discrepancies between different ground-based LAI measurements for heterogeneous and short crop canopies due to the substantial differences in the spatial sampling of transmittance (up to RMSE of 0.16). For shrub and grass land, at least the same error for the LAI measurements is expected, as well as for remote sensing-derived LAI products.…”
Section: Resultssupporting
confidence: 66%
“…For instance, LAI estimates can be derived using the Li-Cor LAI-2000 sensor (Li-Cor, Inc. USA); digital hemispherical photography (DHP) [20]; quantum sensors, such as TRAC (3 rd Wave Engineering, ON, Canada) and Decagon AccuPAR (Decagon Devices, Inc.) or ceptometers (Delta-T devices Ltd, UK). However, hemispherical sensors (such as LAI-2000 and DHP) have been shown to be more robust than other sensors [31,32] in terms of their limited sensitivity to environmental conditions, operational procedures and assumptions, for example in relation to canopy architecture. The LAI-2000 instrument uses a fish-eye lens to measure the canopy light interception in multiple directions at five angles.…”
Section: Validation Of Eo-based Medium Spatial Resolution CCC Productsmentioning
confidence: 99%
“…The digital hemispherical photography technique is based on upward-looking fish-eye photographs taken from beneath the plant canopy that are processed using dedicated software to estimate LAI [34,35]. A detailed review of field techniques for the estimation of LAI can be found in [20,[30][31][32]. Non-destructive estimates of leaf chlorophyll concentration can be obtained from portable leaf chlorophyll meters such as a Minolta SPAD-502 (Minolta Camera Co. Ltd., Japan) or an Opti-Sciences CCM-200 meter (Opti-Sciences, Inc., USA).…”
Section: Validation Of Eo-based Medium Spatial Resolution CCC Productsmentioning
confidence: 99%
“…A variety of approaches for estimating PAI using direct and indirect methods were presented by Bréda [49], Jonckheere et al [50] and Weiss et al [51]. Vegetation gap fraction (G) is defined as the fraction of sky seen from below the canopy [49][50][51][52]. Gap fraction is related to PAI ( 1 .…”
Section: Pai and Fvc Retrievalmentioning
confidence: 99%